Renal hypothermia during partial nephrectomy for patients with renal tumours: a randomised controlled clinical trial protocol. Issue 1 (3rd January 2019) - Breau, Rodney H; Cagiannos, Ilias; Knoll, Greg; Morash, Christopher; Cnossen, Sonya; Lavallée, Luke T; Mallick, Ranjeeta; Finelli, Antonio; Jewett, Michael; Leibovich, Bradley C; Cook, Jonathan; LeBel, Louise; et al.
Abstract : Introduction: Partial nephrectomy is a standard of care for non-metastatic renal tumours when technically feasible. Despite the increased use of partial nephrectomy, intraoperative techniques that lead to optimal renal function after surgery have not been rigorously studied. Clamping of the renal hilum to prevent bleeding during resection causes temporary renal ischaemia. The internal temperature of the kidney may be lowered after the renal hilum is clamped (renal hypothermia) in an attempt to mitigate the effects of ischaemia. Our objective is to determine if renal hypothermia during open partial nephrectomy results in improved postoperative renal function at 12 months following surgery as compared with warm ischaemia (no renal hypothermia). Methods and analyses: This is a multicentre, randomised, single-blinded controlled trial comparing renal hypothermia versus no hypothermia during open partial nephrectomy. Due to the nature of the intervention, complete blinding of the surgical team is not possible; however, surgeons will be blinded until the time of hilar clamping. Glomerular filtration will be based on plasma clearance of a radionucleotide, and differential renal function will be based on renal scintigraphy. The primary outcome is overall renal function at 12 months measured by the glomerular filtration rate (GFR). Secondary outcomes include change in GFR, GFR of the affected kidney, change in GFR of the affected kidney, serum creatinine, haemoglobin, spot urine albumin to creatinine ratio, quality of life and postoperative complications. Data will be collected at baseline, immediately postoperatively and at 3, 6, 9 and 12 months postoperatively. Ethics and dissemination: Ethics approval was obtained for all participating study sites. Results of the trial will be submitted for publication in a peer-reviewed journal. Trial registration number: NCT01529658 ; Pre-results.